SIMPLE SEQUENCE REPEATS IN THE NATIONAL LONGITUDINAL STUDY OF ADOLESCENT HEALTH: AN ETHNICALLY DIVERSE RESOURCE FOR GENETIC ANALYSIS OF HEALTH AND BEHAVIOR - Haberstick, Brett C. (Behav Genet, 2014)
Simple sequence repeats (SSRs) are one of the earliest available forms of genetic variation available for analysis and have been utilized in studies of neurological, behavioral, and health phenotypes. Although findings from these studies have been suggestive, their interpretation has been complicated by a variety of factors including, among others, limited power due to small sample sizes. The current report details the availability, diversity, and allele and genotype frequencies of six commonly examined SSRs in the ethnically diverse, population-based National Longitudinal Study of Adolescent Health (Add Health). A total of 106,743 genotypes were generated across 15,140 participants that included four microsatellites and two di-nucleotide repeats in three dopamine genes (DAT1, DRD4, DRD5), the serotonin transporter (5HTT), and monoamine oxidase A (MAOA). Allele and genotype frequencies showed a complex pattern and differed significantly between populations. For both di-nucleotide repeats we observed a greater allelic diversity than previously reported. The availability of these six SSRs in a large, ethnically diverse sample with extensive environmental measures assessed longitudinally offers a unique resource for researchers interested in health and behavior.